Hypercapitalism : the modern economy, its values, and how to change them - Gonick, Larry; Kasser, Tim (The New Press, 2018)
"From the bestselling cartoonist of The Cartoon History of the Universe comes an explosive graphic takedown of capitalism Bestselling "overeducated cartoonist" Larry Gonick has delighted readers for years with sharp, digestible, and hilarious accounts of everything from the history of the universe to the story of calculus. Now Gonick teams up with psychologist and scholar Tim Kasser, an expert on how happiness and values relate to our materialist society, to create an incomparable cartoon guide to what, exactly, is wrong with modern life, why we're all so miserable-and what can be done about it. Hypercapitalism is an accessible and pointed cartoon guide to the threats to humans, our society, and the environment posed by the current form of global capitalism. A primer for the post-Occupy generation, Hypercapitalism also provides a concise introduction to the thinkers (Stiglitz, Piketty, Sandel, Schor, et al.), movements (voluntary simplicity, the sharing economy, intentional communities, the time-affluence movement), and concepts (hypercapitalism, corporate power, GNP alternatives), that are critical to understanding and changing the world we live in. In pointed, profound, and entertaining cartoon narratives, the authors take readers inside the inner workings of the global economy, rendering even the most complex ideas in clear, plain--and sometimes hilarious--terms"--